Vincristine promotes migration and invasion of colorectal cancer HCT116 cells through RhoA/ROCK/ Myosin light chain pathway - Jin, X.; Liu, K.; Jiao, B.; Wang, X.; Huang, S.; Ren, W.; Zhao, K. (Cellular and Molecular Biology, 2016)
Vincristine is an antitumor vinca alkaloid isolated from vinca rosea, and is a medication used to treat a number of types of cancer. In this study, we investigated the impact of vincristine on oncogenic phenotypes of human colorectal cancer HCT116 cells. MTT assay demonstrated that vincristine showed a obviously inhibitory effect on cell growth compared to non-treated cells. However, Transwell assay showed that vincristine promoted migration and invasion of HCT116 cells in vitro in a concentration-dependent manner between 0.5 and 15 Î¼M vincristine treatment, whereas cell growth showed no remarkable difference within the same concentration range. Additionally, Western blot analysis showed that vincristine significantly elevated RhoA activity and Myosin light chain (MLC) phosphorylation, suggesting the involvement of RhoA/ROCK pathway in the vincristine-induced enhancement of cellular motility. Furthermore, we found that both the siRNA for RhoA and ROCK inhibitor Y27632 attenuated the phosphorylation of MLC, as well as vincristine-induced migration and invasion. These data indicate that vincristine enhanced migration and invasion of HCT116 cells possibly through stimulating RhoA/ROCK/MLC signaling pathway.